Predicting Aggressive Behavior From Exposure to Violence and Emotion Dysregulation in Adolescents - Gong, Jiaowei; Popescu, Andreea (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to examine the predictive roles of exposure to violence and emotion dysregulation in aggressive behavior among adolescents. Methods and Materials: This research employed a correlational descriptive design and was conducted with a sample of 399 Romanian adolescents selected based on the Morgan and Krejcie sample size table. Participants were recruited from secondary schools using stratified random sampling. Data were collected using three standardized instruments: the Aggression Questionnaire (AQ) to assess aggressive behavior, the Children’s Exposure to Violence Scale (CEVS) to measure exposure to violence, and the Difficulties in Emotion Regulation Scale (DERS) to evaluate emotion dysregulation. Data were analyzed using SPSS-27 software. Pearson correlation coefficients were computed to assess the bivariate relationships between variables, and multiple linear regression analysis was used to examine the joint predictive power of the independent variables on aggression. Findings: Descriptive results showed that both exposure to violence and emotion dysregulation were positively correlated with aggressive behavior. Pearson correlation analyses revealed significant relationships between aggression and exposure to violence (r = .48, p < .001), as well as between aggression and emotion dysregulation (r = .55, p < .001). Multiple linear regression analysis indicated that both exposure to violence (β = .31, p < .001) and emotion dysregulation (β = .41, p < .001) were significant predictors of aggressive behavior, accounting for 42.7% of the variance in the dependent variable (R² = .427, F(2,396) = 147.53, p < .001). Conclusion: The findings suggest that both environmental factors such as violence exposure and individual emotional vulnerabilities like emotion dysregulation significantly contribute to adolescent aggression. Interventions targeting emotion regulation skills and reducing exposure to violence may be effective strategies for aggression prevention.